Peran Kajian Kitab Ta’lim Muta’alim dalam Pembentukan Akhlak Santri MAN 1 Surakarta - Tsani, Adzhar Hilman; Salim, Hakimuddin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine the role of the study of the Ta’limul Muta’allim book in shaping the morals of students at MAN 1 Surakarta. Islamic education does not only focus on the mastery of knowledge but also emphasizes the development of character and moral values among students. The book Ta’limul Muta’allim, written by Imam Az-Zarnuji, is one of the classical Islamic texts widely studied in pesantren as a guide to the ethics of seeking knowledge. This research employs a qualitative method with a descriptive analytical approach. Data were collected through interviews, observations, and documentation involving dormitory leaders, teachers of the Ta’limul Muta’allim book, supervisors, and students living in the dormitory of MAN 1 Surakarta. The results of the study show that the study of the Ta’limul Muta’allim book plays a strategic role in shaping students’ moral character by instilling ethical values in the pursuit of knowledge, such as sincere intention, humility (tawadhu’), moral caution (wira’i), and respect for teachers, knowledge, and fellow students. The learning process is implemented through the bandungan method, which allows students to understand the classical text while internalizing the moral values contained in it. The implementation of these values is strengthened through teachers’ exemplary behavior, daily habituation in dormitory life, and a behavioral evaluation system for students. Although several challenges exist, such as limited Arabic language comprehension among new students and the psychological dynamics of adolescence, the study of the Ta’limul Muta’allim book is generally considered effective in supporting the moral development of students in a pesantren-based madrasah environment.